International Treaties In the Czech Legal Order. - Zeman, Ondřej (2007)
In the second, common part describes public international law and it's relation to the national law. Subsequently the system of sources of public international law and application of the international treaties to the system of the national law. In the third, analytical part describes relationship between international and the Czech law, it's historical development and present situation and the relation of the Czech national law to the acquis communautaire as well.